Aransemen Lagu â€œHolan Dak-Danakâ€ Dalam Format Paduan Suara Dengan Iringan Orkestra - Mia Lily Shandy Marbun; Kartini R M Manalu; Kamaluddin Galingging (Musica: Journal of Music, 2025)
This study explores the arrangement of the church song Holan Dak-danak in a choir format with orchestral accompaniment as an effort to enrich the presentation of sacred music in the church. Musical arrangement is understood as a process of reworking a composition by providing variations in harmony, texture, and certain techniques without eliminating the essence of the original song. The song Holan Dak-danak from the Buku Ende was arranged using several techniques such as pizzicato, poco rall, and modulation. In addition, this research also involved the arrangement of other hymns such as Mampirlah Dengar Doaku, Tanganku Na Met-met, Loas Ro Tu Au Dak-danak, and Di Doa Ibuku, which were selected for their theological value and spiritual message. The results show that arranging church songs in choir format with orchestral accompaniment creates a new dimension of musical expression, adds dynamic colors, and enriches the liturgical atmosphere of worship. The inclusion of string, wind, and rhythmic instruments in the arrangement successfully deepens musical interpretation, thereby enhancing the congregationâ€™s appreciation, especially among Sunday school children. This finding confirms that creative arrangements not only beautify the presentation of worship music but also serve as a medium of faith formation and a learning tool for young generations in sacred music